Metabolic syndrome and cognition: A systematic review across cognitive domains and a bibliometric analysis - Koutsonida, Myrto; Markozannes, Georgios; Bouras, Emmanouil; Aretouli, Eleni; Tsilidis, Konstantinos K. (Frontiers in Psychology, 2022)
The aim of this review is to investigate the association between metabolic syndrome and cognitive decline in distinct cognitive domains, and to perform a complementary study description analysis through the bibliometric analysis. PubMed and Scopus databases were searched from inception to 15 December 2021 to identify longitudinal studies that examined the association of metabolic syndrome with incident decline, in order to prevent reverse causality. The Preferred Reporting Items for Systematic Review and Meta-Analysis checklist was used to conduct the present systematic review. Thirty studies were included and results were analyzed across the cognitive domains of global cognition, memory, executive functions, attention, construction and language. The majority of the studies reviewed did not report statistically significant results for most cognitive domains investigated, and decline in specific cognitive domains was not consistently associated with the presence of metabolic syndrome. Meta-analyses were not conducted due to the high degree of between-study heterogeneity regarding the metabolic syndrome definitions, the cognitive domains examined, the specific tests used for each cognitive domain and the different measures of association used. Bibliometric analysis revealed that most studies are conducted by research teams from USA and China, and that cognitive tasks that reflect real-life abilities are rarely examined. Future studies should employ larger sample sizes, longer follow-up periods, a global consensus for metabolic syndrome definition and standardized tests of the above mentioned cognitive domains as well as problem-solving tasks with high sensitivity and specificity to clarify the impact of metabolic syndrome on cognition and its underlying mechanisms.